I'm a high school student from Bonn, Germany and I have to solve the following problem: If $g:R \rightarrow R $ is a function with the property $g(ab)-ag(b)\leq bg(a)$, for all real numbers a and b, then: I. $g(-a)$ is always smaller or equal $-g(a)$ for all real numbers $a$($g(a)+g(-a)\leq0$)? II.The following identity holds: $ag(\frac{1}{a})+\frac{1}{a}g(a)=0$ for all $a>0$. Thank you!

  • $\begingroup$ I presume $\;f\;$ is another real functions...? $\endgroup$ – DonAntonio Feb 22 '14 at 20:07
  • $\begingroup$ Sorry! It's all about the function g. My mistake! $\endgroup$ – Mark S. Feb 22 '14 at 20:32
  • $\begingroup$ You still left a little $\;f\;$ on the right side of the inequality, @Mark ... $\endgroup$ – DonAntonio Feb 22 '14 at 20:42

Since, $g(1)\le2g(1)$ and $g(-1)\le -g(1)+g(-1) \implies g(1)=0$. Also $g(1)\le -2g(-1)\implies g(-1)\le0$.

So, you have $g(-1.a)\le ag(-1)-g(a)$ and $g(-1.-a)\le -ag(-1)-g(-a)$, together adding implies $g(a) + g(-a)\le 0$.(I)

For the second part,$\frac{1}{a}g(a)\le-\frac{1}{a}g(-a)$ and $ag(\frac{1}{a})\le-ag(-\frac{1}{a})$ (using I and $a>0$),by adding we have $0=g(a.\frac{1}{a})\le ag(\frac{1}{a})+\frac{1}{a}g(a)\le -ag(-\frac{1}{a})-\frac{1}{a}g(-a)$ ... (t).

After that I think $g(-1)=0$, is essential to the problem to show that $ag(\frac{1}{a})+\frac{1}{a}g(a)=0$. Because, to show that $ag(\frac{1}{a})+\frac{1}{a}g(a) \le 0$, we need that condition.

Adding, $ag(-\frac{1}{a})-\frac{1}{a}g(a)\ge g(-1)$ and (t), we get $-\frac{2}{a}g(a)\ge g(-1)$. Implying $-2ag(\frac{1}{a})\ge g(-1)$, as well.

That is on adding the last two expressions, $ag(\frac{1}{a})+\frac{1}{a}g(a) \le -g(-1)$, is the best I can get without $g(-1)=0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.